Expert Evaluation of the Organizational Technology for Prolonging Doctors’ Professional Activity - A. V. Vorobeva; M. A. Yakushin (Здоровье мегаполиса, 2024)
Background. Healthcare professionals fall into the professions that significantly strengthen national economy. In order to avoid national economic losses, we should protect older healthcare professionals as a source of national workforce by developing and implementing a health-saving technology that prolongs their professional effective activity. Based on the previously conducted sociological survey of doctors providing medical care in the polyclinics of Moscow and Moscow Oblast, an assessment of the doctors’ professional competencies was carried out [1] and an organizational technology was formed [2] and then submitted to an expert evaluation.Objective. To expertly evaluate the importance of the activities that are included in the organizational technology prolonging the professional effective activity of older doctors.Materials and methods. The methods of sociological, statistical and expert evaluation were used for studying the experts’ opinions on the importance of each activity of organizational technology for prolonging the professional effective activity of healthcare professionals. Experts (n = 50) were asked to rank the activities according to the importance for achieving the result – support for the professional effective activity of doctors - in the case of the implementation of this organizational technology. The experts were specialists in the field of healthcare and public health: chief physicians, heads of departments of polyclinics in Moscow and Moscow Oblast, accredited in the specialty of the Higher Attestation Commission 03.02.03 "Public health, organization and sociology of healthcare, medical and social expertise" with leadership experience in healthcare from 1 to 29 years. The objectivity of experts’ judgment is based on their knowledge and expertise in healthcare and public health.Findings. The experts progressively evaluated the organizational technology, firstly by each stage and then as a whole. Thus, it was made a conclusion on the effectiveness of organizational technology preserving medical competencies and prolonging the professional effective activity of older doctors.